Historical biogeography and cryptic diversity in the Callichthyinae (Siluriformes, Callichthyidae) - Mariguela, Tatiane C.; Alexandrou, Markos A.; Foresti, Fausto; Oliveira, Claudio (Hindawi, 2013)
The family Callichthyidae, divided into the subfamilies Corydoradinae and Callichthyinae, contains more than 200 species of armoured catfishes distributed throughout the Neotropics, as well as fossil species dating from the Palaeocene. Both subfamilies are very widely distributed throughout the continent, with some species ranges extending across multiple hypothesized biogeographical barriers. Species with such vast geographical ranges could be made up of multiple cryptic populations that are genetically distinct and have diverged over time. Although relationships among Callichthyinae genera have been thoroughly investigated, the historical biogeography of the Callichthyinae and the presence of species complexes have yet to be examined. Furthermore, there is a lack of fossil-calibrated molecular phylogenies providing a time frame for the evolution of the Callichthyinae. Here, we present a novel molecular data set for all Callichthyinae genera composed of partial sequences of mitochondrial and nuclear markers. These data were used to construct a fossil-calibrated tree for the Callichthyinae and to reconstruct patterns of spatiotemporal evolution. All phylogenetic analyses [Bayesian, maximum likelihood and maximum parsimony (MP)] resulted in a single fully resolved and well-supported hypothesis for the Callichthyinae, where Dianema is the sister group of all the remaining genera. Results suggest that the ancestry of most Callichthyinae genera originated in the Amazonas basin, with a number of subsequent ancestral dispersal events between adjacent basins. High divergences in sequences and time were observed for several samples of Hoplosternum littorale, Megalechis picta and Callichthys callichthys, suggesting that these species may contain cryptic diversity. The results highlight the need for a taxonomic revision of species complexes within the Callichthyinae, which may reveal more diversity within this relatively species-poor lineage. © 2013 Blackwell Verlag GmbH.
Keywords: Biogeography; Callichthyidae; Cryptic species; Fish; Molecular phylogenetics